Perspective on solving the problem of declining interest in physical activity in Poland - Piepiora, Paweł Adam; Bagińska, Justyna; Piepiora, Zbigniew Norbert (Frontiers in Sports and Active Living, 2024)
One of the leading areas of Polish research addressed in the physical culture sciences, is the declining interest in physical activity. The likely reason for this situation may be the inadequate communication of physical culture to today's generations: BB (baby boomers), X (great unknowns), Y (millennials), Z (snowflakes), Alpha (digital). Therefore, the aim of this article is to address the problem of declining interest in physical activity in Poland by identifying the appropriate approach of teachers, trainers and instructors to today's generations. The specifics of BB, X, Y, Z and Alpha generations are described and their expectations regarding physical activity are indicated. It was concluded that activating these social groups should be done by prompting topics that are important to them. Thus, BB value organizational stability, X need to see the purposefulness and attractiveness of the activities, Y equate physical activity with personal development, Z only take up useful forms of activities, and finally Alpha like smart technology-assisted activities.